Psychometric Properties of the German Version of the Pulmonary-Specific Quality-of-Life Scale in Lung Transplant Patients - Nöhre, Mariel; Albayrak, Özgür; Brederecke, Jan; Claes, Laurence; Smits, Dirk; Tudorache, Igor; de Zwaan, Martina (Frontiers in Psychiatry, 2019)
The Pulmonary-specific Quality-of-Life Scale (PQLS) is a validated self-report questionnaire assessing health-related quality of life (HRQoL) in patients with end-stage lung disease awaiting lung transplantation. The aim of our study was to evaluate the psychometric properties of the German version of the PQLS. One hundred and forty patients awaiting lung transplantation (55% men) with a median age of 53 years (IQR 13) answered the PQLS. A small group of the participants (n=43) was evaluated again one year later after transplantation. A confirmatory factor analysis (CFA) of the PQLS was conducted to test the three factor structure of the PQLS. We examined the internal consistency of the scales using Cronbach’s α. Convergent validity was explored through correlations with generic measures of HRQoL (Short-Form 8 Health Survey (SF-8), 10-item QoL scale), measures of depression (9-item Patient Health Questionnaire-Depression Scale (PHQ-9)), anxiety (Generalized Anxiety Scale (GAD-7)), and measures of lung disease severity (supplemental oxygen use, stairway steps). In the group of 43 patients assessed before and after transplantation, sensitivity to change was explored. The CFA confirmed the three-factor model with an acceptable fit. The PQLS total and the three subscale scores “task interference”, “psychological”, and “physical” showed acceptable internal consistency. The PQLS and its subscales showed a significant negative correlation with the 10-item QoL measure and the physical component score of the SF-8, whereas the mental component score of the SF-8 showed a significant negative correlation only with the PQLS subscale “psychological”. Negative correlation were found due to the opposed alignment of the PQLS compared to the 10-item QoL and the SF-8. Symptoms of depression and anxiety were significantly and positively correlated with the subscale “psychological”. Measures of lung disease severity also exhibited a significant positive correlation with the subscales “task interference” and “physical” but not “psychological”. In patients one year after a successful transplantation, the PQLS scores were significantly reduced by 50%. The 3-factor structure of the PQLS could be replicated using CFA. The results indicate good reliability, validity, and sensitivity to change of the German version of the PQLS.